Learn 2 live - live 2 learn : the re-use of the UP Mamelodi campus and the stitching together of landscapes as a vehicle for empowerment - Breed, Ida (University of Pretoria, 2013)
Dissertation (ML(Prof))--University of Pretoria, 2008.